(untitled) (International Journal of Educational Management, Rivers State University., 2025)
There is no doubt that the proliferation of social media across various levels of education in the world has raised concerns among stakeholders regarding its impact on student academic performance. This study investigated the effect of three different social media platforms (YouTube, WhatsApp, and Google) on the academic performance of public secondary school students in Port Harcourt, Rivers State. The study contributed to the existing body of knowledge on the impact of social media on academic performance in Port Harcourt. At the same time, developing strategies and insights on maximizing the benefits and minimizing the cost of social media usage among students. A combined research design of descriptive survey and qualitative data collection (structured interview) was used to elicit respondents’ opinions (300 students and 100 teachers). The findings revealed that excessive and improper use of YouTube and WhatsApp by students negatively impacts the academic performance of students as expressed in a grand mean of 2.16 and 1.89 respectively. Google positively impacts students’ academic performance when used for academic purposes with a grand mean of 3.76. Based on these findings, the study recommends that educators and parents monitor students’ social media usage to promote the responsible use of these platforms to enhance academic performance.